2000
DOI: 10.1038/oby.2000.70
|View full text |Cite
|
Sign up to set email alerts
|

Percent Body Fat and Lean Mass Explain the Gender Difference in Leptin: Analysis and Interpretation of Leptin in Hispanic and Non‐Hispanic White Adults

Abstract: MARSHALL, JULIE A., GARY K. GRUNWALD, WILLIAM T. DONAHOO, SHARON SCARBRO, AND SUSAN M. SHETTERLY. Percent body fat and lean mass explain the gender difference in leptin: analysis and interpretation of leptin in Hispanic and non-Hispanic white adults. Obes Res. 2000;8:543-552. Objective: To reassess the relationship between body fat and fasting leptin concentrations comparing plasma vs. serum assessments of leptin; ratios vs. regression adjustment for body composition; fat and lean mass vs. percent body fat; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 44 publications
(66 reference statements)
8
25
0
1
Order By: Relevance
“…We confirmed this evidence using two parallel statistical analyses based on multiple linear regression models and SEqM (5). In our population, plasma levels of adiponectin, osteocalcin, and leptin were significantly higher in women, in agreement with other population studies (15)(16)(17). Our finding of a negative association of adiponectin with insulin resistance is also consistent with results from other human studies (18,19).…”
Section: Discussionsupporting
confidence: 95%
“…We confirmed this evidence using two parallel statistical analyses based on multiple linear regression models and SEqM (5). In our population, plasma levels of adiponectin, osteocalcin, and leptin were significantly higher in women, in agreement with other population studies (15)(16)(17). Our finding of a negative association of adiponectin with insulin resistance is also consistent with results from other human studies (18,19).…”
Section: Discussionsupporting
confidence: 95%
“…Marshall et al and others previously reported higher muscle mass in Blacks compared to Whites [18,19]. Comparable to our observation of -2.88 kg mean difference in FFM between white women and black women in this study, Gallagher et al reported -2.22 kg difference in FFM between these 2 groups of women [17].…”
Section: Discussionsupporting
confidence: 58%
“…The gender differences in circulating leptin were best explained by percentage of body fat and – inversely – by lean body mass [25]. In both genders the intra-abdominal fat correlated with insulin resistance, while the subcutaneous fat correlated with circulating leptin [11,12].…”
Section: Discussionmentioning
confidence: 99%